Multifunctional Nanoprobes From Design Validation to Biomedical Applications - Liu, Yanlan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This thesis mainly focuses on the design and synthesis of novel multifunctional nanoprobes, investigating their feasibility for applications involving sensing, molecular imaging, and the simultaneous diagnosis and therapy of cancer. Above all, it discusses the development of innovative nanomaterials to address the issues limiting the effectiveness of currently available nanoprobes such as the synthesis shortcoming and poor performance in sensing, imaging and therapeutic applications. One of the strengths of this thesis is its integration of knowledge from chemistry, materials science and biomedicine. Further, it presents the theoretical fundamentals in the design of nanoprobes, which can offer guidance for future studies on the development of novel multifunctional nanomaterials with significantly enhanced performance.
Gold Nanocluster-Based Fluorescent Sensor for Highly Sensitive and Selective Detection of Cyanide in Water -- Fluorescence-Enhanced Gadolinium-Doped Zinc Oxide Quantum Dots for Magnetic Resonance and Fluorescence Imaging.- High-performance Ytterbium-based Nanoparticulate Contrast Agent for In Vivo X-ray Computed Tomography Imaging -- Hybrid BaYbF5 Nanoparticles: Novel Binary Contrast Agent for High-Resolution in Vivo X-ray Computed Tomography Angiography -- Dopamine-Melanin Colloidal Nanosphere: An Efficient Near-Infrared Photothermal Therapeutic Agent for In Vivo Cancer Therapy -- Bi2S3 Nanodots for X-ray CT Imaging Guided Photothermal Therapy of Cancer -- Summary. p>.
Keywords: Nanotechnology; Biomedical engineering; Cancer; Analytical chemistry; Biomaterials; Nanotechnology; Biomedical Engineering and Bioengineering; Cancer Biology; Analytical Chemistry; Biomaterials